Development of Tuition Centre Management System via Mobile App - Kamaroszaman, Putera Ezzalee; Saringat, Dr. Mohd Zainuri (Applied Information Technology And Computer Science, 2022)
Tuition Centre is a private institution for education as an addition to school. It is not mandatory to enroll for tuition in any tuition centre, but most parents send their children to prepare for examinations such as SPM, UPSR, PT3 or STPM. The system titled Tuition Centre Management System via Mobile Application should be able to grasp the needs for tuition centre to manage their students and for parents to manage their children enrolling in them. Problem arisen led to the idea of building the system is the fact that it is hard to track the understanding of student on the subject they are enrolling. Hence the system would generate the student performance on certain subject to monitor their performance. Attendance is taken using traditional way which is very much flawed easily exploited. The proposed way is by using QR code scanner where each student could only by their own account. Other than that, the parents are not not notified by their children performance on hand as well as attendance on classes. As a solution the app would be available not only for tutor and students but also for parents. This system would be developed by using an object-oriented software development approach as the methodology which expected to be able to produce a system which helps in managing the students in tuition centre regarding their performance and attendance.